Football Shooting Accuracy at Olang Soccer School: Target Training (Department of Physical Education, Sport, Health and Recreation, 2023)
The purpose of the study was to determine the effect of target training on football shooting accuracy at Olang Soccer School. The method used in this study is an experimental method. The population in this study was 50 Olang Soccer School athletes. Sampling using porposive sampling with certain considerations by the researcher. The study sample was determined based on the level of the age group of 15 to 17 years which amounted to 20 people. Test instruments carried out to measure shooting accuracy are target training Goaling, Sleigh Shooting, Bolbal Shoot. The data analysis techniques used are descriptive analysis, normality test, paired sample t-test using the SPSS application program version 23.00. The results of the study were the value of t = count of 10.018 > t = table 2.086 and the results of sig. (2-tailed) which is 0.000 < 0.05. The conclusion is that there is a significant effect of target training on the shooting accuracy of Olang Soccer Scholl.